EXPLORING THE ROLE OF EMOTIONAL INTELLIGENCE IN ADOLESCENT DEVELOPMENT: IMPLICATIONS FOR EDUCATIONAL PRACTICES - Rinovian Rais; Syarifatul Hayati Zarfi; Nina Anis (World Psychology, 2026)
Emotional intelligence (EI) is increasingly recognized as a critical factor in adolescent development, influencing various aspects of social, emotional, and academic growth. Adolescence is a developmental stage marked by significant emotional and social changes, which makes the role of EI in shaping behavior and decision-making particularly important. Understanding how EI contributes to adolescent development can help inform educational practices aimed at fostering emotional and social competencies. This study explores the role of EI in adolescent development and its implications for educational practices. The research employs a mixed-methods approach, combining quantitative assessments of EI using the Bar-On Emotional Quotient Inventory (EQ-i:YV) and qualitative interviews with teachers and students. The findings indicate that higher EI levels are associated with better academic performance, enhanced peer relationships, and improved emotional regulation. Adolescents with higher EI demonstrated greater resilience in managing stress and navigating social conflicts. The study concludes that incorporating EI-focused strategies into educational curricula can enhance students' emotional and social development, thereby improving both academic outcomes and overall well-being. The study suggests that emotional intelligence should be a central component of educational practices to support holistic adolescent development.